Análise da gestão do processo de projeto estrutural de construções metálicas - Renata Bacelar Teixeira (2007)
This paperwork analyzes and promotes a diagnosis of the structural process of metallic constructions. As a tool, we used the interviewing method, making interviews with important offices that are specialized in metallic structures in Belo Horizonte area. The other agents involved in buildings that use metallic structures in Belo Horizonte area were also interviewed, since they also influence the process of structural projects of metallic construction. A study of cases was made and illustrates some characteristics diagnosed about the structural project process of its constructions. We also show up some frequent problems that have its causes in the process of metallic construction project failures. As a result, we develop analysis of some aspects of the process of metallic construction project, such as the palnning of the building, the structural project development, the relationshisp between projectors and documentation management. We conclude that the process of metallic construction project is inefficient in many aspects, and we can detach: late choice of the metallic structural system, deficiency in tlhe projects development and poor specification of constructive industrialized materials complementary to the metallic structure. In this way, the quality of tlhe building that uses metallic structures is shortened, showing evidences that advances in the process of metallic construction project are needed, and, specially, advances in tlhe structural project process. We hope that this paperwork can contribute to the advance of tlhe researches turned to the process of metallic construction project. We also hope that it promotes a larger knowledge about the influence of process of metallic construction project in the final quality of buildings.